The determining factors of service value and satisfaction for edutainment services in Malaysia - Indra, Balachandran (2014)
Edutainment is a growing business in our country and it is precisely to study the service value and satisfaction to learn about customers behaviors. The purpose of this study is to identify antecedents of service value and satisfaction and determine the relationship and which antecedents are most influential on value and satisfaction. This research used a nonprobability with mall intercept convenience sampling and 130 respondents were participated in this survey. This study employed the Descriptive analysis, Correlation analysis, and Multiple Regression Analysis. For the data analysis, we have used 127 questionnaires and 7 questionnaires were eliminated due to incomplete. The results of this study are supported that overall service marketing mix and service quality have a positive and significant relationship between service value and service satisfaction. Meanwhile, the most influential antecedents on value are the physical evidence and service quality, for service satisfaction is the service quality. Our research suggests that the edutainment marketing managers should create an effective service marketing mix strategies which leads to customer perceived quality, perceived value as well as perceived satisfaction.